2019
DOI: 10.1002/macp.201800477
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Application of Functionalized Diblock Amphiphilic Fullerene Derivatives

Abstract: A series of functionalized amphiphilic diblock fullerene derivatives C60‐4TPB, C60‐2DPE, C60‐4HTPB, C60‐PHFBS, and C60‐2BEFPE are developed and applied as the modification layers on zinc oxide (ZnO) in inverted organic solar cell (OSC) devices. By spin‐coating ZnO, the fullerene derivatives layer can reduce the work function of ZnO via modulation of the interfacial dipoles. When introducing solvent treatment by toluene during the preparation of films, the order of the fullerene derivatives layer are clearly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…With the continuous development of nanotechnology, the application of nanomaterials and 2D materials will become extensively wider, especially fullerene materials, which can be used not only as acceptor materials but also as interfacial materials by introducing different side chains. For example, the charges’ extraction and transport are increased by the addition of an n-type (or p-type) doping group; the defects could be induced and carrier recombination could be prevented by introducing the hydrophilic side chain . In addition, we can ascertain that there are much less AIL materials than CIL materials from this review, and the commonly used AILs are only PEDOT:PSS and MoO 3 .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…With the continuous development of nanotechnology, the application of nanomaterials and 2D materials will become extensively wider, especially fullerene materials, which can be used not only as acceptor materials but also as interfacial materials by introducing different side chains. For example, the charges’ extraction and transport are increased by the addition of an n-type (or p-type) doping group; the defects could be induced and carrier recombination could be prevented by introducing the hydrophilic side chain . In addition, we can ascertain that there are much less AIL materials than CIL materials from this review, and the commonly used AILs are only PEDOT:PSS and MoO 3 .…”
Section: Discussionmentioning
confidence: 90%
“…In addition, the studies have shown that these materials could passivate the defects of the ZnO interlayer, hence fabricating a hybrid ETL with better quality. Liu et al incorporated C 60 -4TPB, C 60 -2DPE, C 60 -4HTPB, C 60 -PHFBS, and C 60 -2BEFPE between ZnO and the active layer, achieving the PCE of 8.62%, 9.21%, 8.86%, 9.14%, and 9.15%, respectively . Additionally Kumar et al obtained a 60% enhancement concerning PCE by depositing C 70 on ZnO film …”
Section: Nanostructure and Two-dimensional Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the fullerene derivatives showed a self‐assembly on the ZnO X layer, which improved the contact between ZnO X and active layer. Finally, these fullerene derivatives can passivate the ZnO X surface, optimize ZnO X WF , and suppress charge recombination losses in solar cell devices, improving V OC and J SC …”
Section: Fullerene‐based Small Molecular Interlayersmentioning
confidence: 99%
“…Based on the characteristic of low work function, zinc oxide (ZnO) was always used as a buffer layer to decrease the barrier of the cathode electrode with an ohmic contact in inverted OSCs. However, the trap sites and defects of ZnO always required an amphiphilic interface material to be introduced between ZnO and the active layer to get an efficient device. The most commonly used interface material to modify ZnO was the amphiphilic organic material, especially the functionalized amphiphilic fullerene derivatives. Amphiphilic fullerene derivatives functionalized with polar groups can be regarded as hydrophobic–hydrophilic diblock molecular, in which fullerene and polar groups were the hydrophobic and hydrophilic blocks, respectively. The introduced amphiphilic diblock fullerene derivative layer can also guarantee the improvement of interface compatibility when introducing to modify ZnO in OSC devices. …”
Section: Introductionmentioning
confidence: 99%